Enhancing Historical Thinking Skills of High School Students in Bandar Lampung through Interactive Learning Modules Using Liveworksheet - Maftuchin; Sinaga, Risma Margaretha; Istiawati, Novia Fitri; Widodo, Sugeng; Adha, Muhammad Mona (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
History subjects have a role in building historical awareness and preventing learners from being blind to historical values. This condition requires teachers to involve students in interpreting and analyzing historical artifacts and primary sources, as well as constructing and criticizing narratives about the past. This study aims to determine the feasibility and effectiveness of developing an interactive module based on Liveworksheet in constructing history learning to improve the historical thinking ability of high school students in Bandar Lampung City. The research method used is Research and Development (R&D), adopting the ADDIE development model. This research was conducted at SMA Negeri 7 Bandar Lampung and SMA YP Unila Bandar Lampung. The validity of the material, media, and design, as well as the small group test of the Liveworksheet-based interactive learning module, yielded an average score of 95.2%, categorized as very feasible. The effectiveness of the Liveworksheet-based interactive learning module in improving the historical thinking ability of high school students in Bandar Lampung City is evidenced by the increase in pretest and posttest results. Based on the feasibility validation results, a significant score of 95.2% was obtained, indicating a very feasible module. Additionally, the effectiveness of the development reached 95.5%, showing that the Liveworksheet-based interactive learning module has a significant impact on improving the historical thinking skills of high school students in Bandar Lampung City, with criteria categorized as very effective.